Le français dans l’écriture conradienne - Claude Maisonnat (Cahiers Victoriens et Edouardiens)
Conrad chose English, his third language, to write some of the masterpieces of literature in English, yet French was familiar to him and remarkably mastered by him from an early age. His knowledge and practice of the language have long been extensively documented from his childhood to his four-year stay in Marseille and the numerous letters he wrote in French to friends, family, fellow writers and translators during his whole life. The aim of this essay is to show that although he never wrote a line of fiction in French, the latter is omnipresent not only in his fiction, through characters, locations, dialogues, quotations, intertextual borrowings, but most of all in the highly idiosyncratic medium of his prose, mainly in the guise of Gallicisms and occasionally erroneous loan translations. The result is that French is essential to his art in so far as it provides a constant challenge to the master discourse of the authorial voice and thus constitutes the basis of the poetic dimension of his prose based on the Lacanian notion of lalangue, as if French acted as a surrogate maternal language.